2015
DOI: 10.3389/fmicb.2015.00291
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic diversity of clinical Vibrio parahaemolyticus isolates from China, revealed by multilocus sequence typing scheme

Abstract: The population structure of clinical Vibrio parahaemolyticus isolates spreading in China remains undefined. We brought 218 clinical isolates from the pubMLST database originating from different regions of China collected since the year of 1990, analyzed by multilocus sequence typing (MLST), to elucidate the prevalence and genetic diversity of V. parahaemolyticus circulating in Chinese population. The MLST scheme produced 137 sequence types (STs). These STs were clustered into six clonal complexes (CCs), six do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…In the present study, we showed that the population structure of V. parahaemolyticus was extremely genetically diverse based on the successful identification of 19 CCs and a large number of singletons, in agreement with previous findings (Han et al, 2015 ). Over half of the pandemic STs belonged to CC3 according to goeBURST analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we showed that the population structure of V. parahaemolyticus was extremely genetically diverse based on the successful identification of 19 CCs and a large number of singletons, in agreement with previous findings (Han et al, 2015 ). Over half of the pandemic STs belonged to CC3 according to goeBURST analysis.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, we successfully made extensive descriptions of strains from a global clinical collection and from Chinese patients, respectively, exhibiting a highly degree of genetic diversity and a complicated population structure of V. parahaemolyticus in general (Han et al, 2014 , 2015 ). In this study, we elucidated the sero-prevalence and genetic differentiation of the pandemic clone, which has becoming an emerging public health concern (Martinez-Urtaza et al, 2010 ; Velazquez-Roman et al, 2012 , 2014 ; Powell et al, 2013 ; Li et al, 2014 ; Pazhani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gyrB locus was the most diverse, with 87 alleles, while possessing only 63 (10.6%) variable sites. This is consistent with the findings of previous studies [ 18 , 19 ]. The dN/dS values of each locus were all lower than 1.0, revealing that these loci had been subjected to purifying selection [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies already used MLST analysis to characterize V. parahaemolyticus strains, and some researchers also evaluated the epidemiology of this pathogen in China [ 18 ]. The strains used in some studies had a global distribution [ 19 , 20 ], with a focus being placed on both clinical and environmental isolates [ 21 ].…”
Section: Discussionmentioning
confidence: 99%